DKK1 expression by synovial fibroblasts in very early rheumatoid arthritis associates with lymphocyte adhesion in an in vitro flow co-culture system. Issue 1 (December 2016) - Juarez, Maria; McGettrick, Helen; Scheel-Toellner, Dagmar; Yeo, Lorraine; Spengler, Julia; de Paz, Banesa; Hardy, Rowan; Cooper, Mark; Raza, Karim; Buckley, Christopher; Filer, Andrew
Abstract Background Synovial fibroblasts play a key role in joint destruction and regulation of the inflammatory infiltrate in established rheumatoid arthritis (RA). The mechanisms by which this occurs in the earliest stages of RA are largely unknown. We investigated the role of Dickkopf-related protein 1 (DKK1) produced by synovial fibroblasts of patients with very early rheumatoid arthritis (VeRA). Methods Fibroblasts were isolated from the disease-modifying anti-rheumatic drug–naive Birmingham early arthritis cohort of patients with new onset of clinically apparent arthritis and inflammatory symptoms of ≤12 weeks' duration, who at follow-up had either resolving arthritis or RA. Endothelial fibroblast co-cultures were formed using porous filters, and lymphocyte adhesion to co-cultures was assessed using phase-contrast microscopy. DKK1 gene expression and secretion were quantified by quantitative polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. Results Synovial fibroblasts from patients with VeRA expressed significantly higher levels of DKK1 messenger RNA than those from patients with resolving arthritis. A similar trend was observed for DKK1 protein secretion. In co-culture constructs, more DKK1 tended to be secreted in co-cultures incorporating fibroblasts from VeRA than in co-cultures from non-inflamed joints and resolving arthritis. DKK1 secretion during co-culture positively correlated with lymphocyte adhesion. Conclusions Alterations in DKK1 could be involved in the pathogenesis and perpetuation of the inflammatory response in the earliest clinically apparent stages of RA.